1988
DOI: 10.1002/bbpc.198800335
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5,10,15,20‐Tetrakisphenylporphins on a Carbon Support for the Cathodic Reduction of Oxygen in Fuel Cells

Abstract: Several substituted Fe-and Co-containing tetraphenylporphins 1 were loaded on carbon either by adsorption from acetone or by in situ synthesis on the carbon support. The porphin/carbon combinations were pyrolyzed at 800 "C, The electrocatalytic activities in the reduction of dioxygen were investigated in alkaline (KOH) and aeid (H 2S04 ) solutions using porous Teflon-bonded earbon electrodes impregnated with the catalysts. At 700 mV high current densities of 75 mA/cm 2 in acid solution and up to 90 mA/em 2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…In the case of the Fe compound, by interpretation of X-ray photoelectron spectroscopy (XPS) data, it was shown that optimal activity was obtained for 10% w/w loading, corresponding to a monolayer coverage. In contrast to the data obtained on porphyrins [23], samples with 20% loading were less active.…”
Section: Introductioncontrasting
confidence: 99%
“…In the case of the Fe compound, by interpretation of X-ray photoelectron spectroscopy (XPS) data, it was shown that optimal activity was obtained for 10% w/w loading, corresponding to a monolayer coverage. In contrast to the data obtained on porphyrins [23], samples with 20% loading were less active.…”
Section: Introductioncontrasting
confidence: 99%
“…1b, one can see the typical absorption peak corresponding to the emeraldine state of PANI at ∼800 nm. [40][41][42] This peak shows an enhancement and a slight red shift from ∼790 nm (0 °C) to ∼805 nm (20 °C) as the temperature increased. It is well known that the UV-Vis absorbance band shifts at longer wavelengths with a longer conjugated molecular chain.…”
Section: Resultsmentioning
confidence: 99%
“…1) exhibit two sets of absorption peaks. One is a shoulder observed at ∼430 nm which corresponds to an intermediate redox state of PANI, the other one is a broad band centered at ∼800 nm which is ascribed to the emeraldine state of PANI [40][41][42] and compared as a signature of the formation of conductive PANI due to polaron band transitions. 4,41 The UV-Vis spectra of PANI synthesized at the pH range of 1.5-3.2 are given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An approach in which pyrolyzed transition metal macrocycles are used as cathode catalysts, in the struggle against methanol crossover, have proven significant activities towards oxygen reduction. Out of these Fe and Co porphyrins and their derivatives appear to be the most active [74,75]. The results obtained by Wang et al also proved that carbon…”
Section: Figure 26 Reaction Mechanisms For Oxygen Reduction [70]mentioning
confidence: 84%